Application of Ribbon Quilling Sakura Flower Embellishment on Daytime Party Dress as a Center of Interest - Riza Afriliah; Cucu Ruhidawati (Universitas Negeri Semarang, 2025)
This study aims to explore the application of ribbon quilling technique as a decorative element in fashion design, focusing on cherry blossom motifs applied to a daytime party dress. Quilling, originally a 17th-century European paper craft, is adapted using grosgrain ribbon to create flower-shaped ornaments with a soft and elegant visual character. The novelty of this research lies in the use of ribbon-based quilling as an alternative approach for decorating formal wear, which has been scarcely explored in fashion design practice. This study employs a practice-led research approach through four main stages: exploration, design, realization, and evaluation. The exploration stage involves gathering visual references and adapting the quilling technique to the characteristics of grosgrain ribbon; the design stage includes sketch development and ornament placement; the realization stage covers the creation and application of quilling on the dress; and the evaluation stage is conducted based on the principles of unity, balance, and proportion by a fashion design expert. The results demonstrate that ribbon quilling technique can enhance the aesthetic value of formal wear by combining handcrafted skills with contemporary design approaches. These findings open opportunities for further development in accessories, costumes, and bridal wear, as well as contributing to fashion education and the preservation of handcraft-based decorative techniques.